Pengaruh Pengumuman Kabinet Kerja Joko Widodo Terhadap Perubahan Reaksi Pasar Modal Pada Perusahaan Manufaktur Di Bursa Efek Indonesia - Sari, Putri Novita; , Dr. Triyono, M.Si (2015)
This study aimed to get empirical evidence and determine the effect of the Cabinet Working Joko Widodo Announcement on Changes in Capital Market Reaction Manufacturing Company in Indonesia Stock Exchange with a sample of manufacturing firms that have qualified are listed on the Stock Exchange in the period in 2014. The number of samples in this study as many as 85 companies listed in the Indonesia Stock Exchange that have met the criteria. The samples in this study was done by using purposive sampling method. From the analysis it can be concluded that the data were normally distributed and can be followed by t-test. The results showed (1) the average value Abnormal return 5 days before the announcement of the Cabinet Working Joko Widodo -0.017958036 increased to -0.022725164 fifth day after the announcement of the Cabinet Working Joko Widodo, (2) the average Trading Volume Activity 5 days before the announcement of the Cabinet Working Joko Widodo 0.000571515 increased to 0.000556767 fifth day after the announcement of the Cabinet Working Joko Widodo, (3) there were significant differences Abnormal return before and after the announcement of the Cabinet Working Joko Widodo with a significance value of 0.037 and (4) there was a significant difference Trading Volume Activity before and after the announcement of the Cabinet Working Joko Widodo with a significance value of 0.012. Keywords: Announcement Cabinet Work Joko Widodo, Abnormal Return, Trading Volume Activity